Teses oor geskiedenis? – Oor onreg, oordeel en eskatologie - Smit, Dirkie (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The paper is an annotated version of an originally oral contribution during an international and inter-disciplinary consultation on “Injustice, Judgment and Eschatology” hosted in the Theology Faculty of Stellenbosch University on August 3, 2012. It revisits the life and work of Walter Benjamin, the Jewish philosopher and author from Berlin who combined these three notions in a remarkable way and with lasting impact in literary, artistic, cultural and philosophical circles, until today. The essay serves as reminder of Benjamin’s last writing before his death in 1940, namely the influential eighteen theses on history. It briefly illustrates how challenging, influential and inspiring these aphoristic theses have been and still remain, precisely by linking these three notions of injustice, judgment and eschatology in complex ways. It particularly points to the ninth thesis, interpreting Paul Klee’s Angelus Novus as the angel of history. The essay is deliberately also written in the form of eighteen brief theses, as formal reminder of Benjamin’s remarkable and incomparable style.